Production and marketing of cassava flour for human consumption in Colombia : summary of final report: Pilot project phase (June 1989-December 1991) - Ostertag Gálvez, Carlos F.; Wheatley, Christopher C. (International Center for Tropical Agriculture, 1992)
This report corresponds to Phase 2 (pilot project) of an Integrated Cassava Project whose general objective is the creation of a rural agroindustry that produces cassava flour for human consumption. In Phase 1 (Research), the main objective was to determine the technical and economical conditions required for the development of a rural cassava flour agroindustry. In summary, the process designed has the following steps: selection and preparation of cassava roots, mechanical washing, chipping, artificial drying, premilling, milling, sieving, and packaging. The second phase sought to integrate the production, processing and marketing components of the cassava flour system under the real socioeconomic conditions at Chinú, a cassava-growing region of the Córdoba department in the Atlantic coast of Colombia. As the project conclusion, the feasibility study of the cassava flour agroindustry considers the following four areas: technical feasibility (the process), commercial feasibility (the market), feasibility of management by farmers, and the financial feasibility (return on investment). The main recommendations proposed to promote the project`s feasibility are: to lower microbial contamination of roots, reduce labor consumption in the preparation operation to 20 man-hours, redesign the drying system inspired in the one at CIAT, guarantee the supply of raw material during the period from June to September, to hire a professional with knowledge of food technology who can coordinate marketing, implement the profitability strategy to raise the FRR above 50 percent. These improvements or modifications are expected to be implemented during 1992.